MARKETING TRENDS IN THE DATA ECONOMY (2024–2025) - Svetlana V. Koshevenko (Наука Красноярья)
Marketing development trends depend on many factors: the level of digitalization and digital transformation of the economy, the development of social networks and digital platforms, mobile marketing and the willingness of companies to implement innovations. To maintain competitiveness, companies must follow trends:  be aware of changes in the market, monitor scientific discoveries and new technologies. Trends allow not only to make more profit, but also to improve customer services, increase the loyalty of existing customers and win new ones. Today, Russia is in a situation where foreign brands have left the market, freeing up niches; digital technologies are developing dynamically, the digital economy is being replaced by the data economy; an increasing number of users are "going online", preferring to make purchases online. All this indicates the need for a qualitative change in marketing strategies. Marketing specialists must have a good understanding of market movements, detect changes in consumer behavior and select the most effective tools for brand promotion and development. In this study, we analyzed the main marketing trends of 2024 and outlined the prospects for the development of trends in 2025.